Human Rights Reasoning and Medical Law: A Sceptical Essay. (19th February 2014) - Wall, Jesse
Abstract I am sceptical as to the contribution that human rights can make to our evaluation of medical law. I will argue here that viewing medical law through a human rights framework provides no greater clarity, insight or focus. If anything, human rights reasoning clouds any bioethical or evaluative analysis. In Section 1 of this article, I outline the general structure of human rights reasoning. I will describe human rights reasoning as (a) reasoning from rights that each person has 'by virtue of their humanity', (b) reasoning from rights that provide 'hard to defeat' reasons for action and (c) reasoning from abstract norms to specified duties. I will then argue in Section 2 that, unless we (a) re‐conceive of human rights as narrow categories of liberties, it becomes (b) necessary for our human rights reasoning to gauge the normative force of each claim or liberty. When we apply this approach to disputes in medical law, we (in the best case scenario) end up (c) 'looking straight through' the human right to the (disagreement about) values and features that each person has by virtue of their humanity.